Three-dimensional constitutive model of woven fabric-reinforced shape memory polymer composites considering thermal residual stress. (5th February 2019) - Hong, Seok Bin; Jang, Joon Hyeok; Park, Haedong; Kim, Jin-Gyun; Goo, Nam Seo; Yu, Woong-Ryeol
Abstract: The mechanical modeling and simulation of woven fabric-reinforced shape-memory polymer composites (wf-SMPCs) are quite complex tasks because a temperature change introduces thermal stress that dramatically affects the interaction between the matrix and fiber. This study aimed to develop a new homogenized constitutive model for wf-SMPCs considering the thermally induced residual stress. The orthotropic properties of the wf-SMPC due to the woven fabric reinforcement were modeled using classical anisotropic hyperelasticity theorems. The stress generated in the hyperelastic model was then complemented by combining with the stress generated in the SMP constitutive equation and the thermal residual stress according to Eshelby's inclusion theorem. The prediction capability of the proposed model was verified by three-point bending tests of the wf-SMPC having various fiber volume fractions. Finally, the unique features of the proposed constitutive model were investigated by experiments and simulation of a self-deployable antenna made of a wf-SMPC.